2009
DOI: 10.1038/nbt1519
|View full text |Cite
|
Sign up to set email alerts
|

Protein promiscuity and its implications for biotechnology

Abstract: Molecular recognition between proteins and their interacting partners underlies the biochemistry of living organisms. Specificity in this recognition is thought to be essential, whereas promiscuity is often associated with unwanted side effects, poor catalytic properties and errors in biological function. Recent experimental evidence suggests that promiscuity, not only in interactions but also in the actual function of proteins, is not as rare as was previously thought. This has implications not only for our f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
393
1
4

Year Published

2010
2010
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 456 publications
(402 citation statements)
references
References 117 publications
4
393
1
4
Order By: Relevance
“…[3][4][5] Previous studies have suggested structural flexibility through large disordered regions, [6][7][8][9] and distributed surface charge, especially in small hubs (less than 300 residues) with no disordered regions. 9,10 The presence of multiple domains in hubs has also been suggested, 11,12 the reasoning being that multiple domains correspond to multiple interaction interfaces 13 and greater functional complexity. 14 Indeed, several hubs have multiple domains containing several binding sites.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Previous studies have suggested structural flexibility through large disordered regions, [6][7][8][9] and distributed surface charge, especially in small hubs (less than 300 residues) with no disordered regions. 9,10 The presence of multiple domains in hubs has also been suggested, 11,12 the reasoning being that multiple domains correspond to multiple interaction interfaces 13 and greater functional complexity. 14 Indeed, several hubs have multiple domains containing several binding sites.…”
Section: Introductionmentioning
confidence: 99%
“…Enzymes are commonly viewed as highly specific for their natural substrates; however, this view obscures the fact that many have the ability to perform multiple activities (1,2). This "promiscuity" typically involves the same chemistry applied to different substrates or, alternatively, can use different catalytic machinery within the same active site (3,4).…”
mentioning
confidence: 99%
“…5 The gold standard to identify these residues remains systematic mutational analysis, [6][7][8] but this approach has some high throughput limitations. Inadequate choice and availability of assays reduce sensitivity while the promiscuity of binding 9 or catalysis, 10 as well as poor reproducibility of the relevant cellular context, 11 reduce specificity.…”
Section: Introductionmentioning
confidence: 99%